Emergency tracheostomy for failed intubation due to glottic stenosis. Issue 2 (26th February 2021) - Yap, Tessa; Quick, Mark; Moore, Paige
Abstract : Glottic stenosis can be an unexpected finding during an intubation, causing difficulties that may result in a 'can't intubate, can't ventilate' situation. We present a case of a patient who required an emergency tracheostomy, in the setting of a failed intubation secondary to glottic stenosis. The patient underwent open laryngotracheal reconstruction, followed by tracheostomy decannulation 2 months post-surgery. This paper highlights the importance of awareness of laryngeal pathology masquerading as respiratory conditions. It also outlines the critical approach to managing 'can't intubate, can't ventilate' situations.